AgNPs Change Microbial Community Structures of Wastewater - Guo, Yuting; Cichocki, Nicolas; Schattenberg, Florian; Geffers, Robert; Harms, Hauke; Müller, Susann (Frontiers in Microbiology, 2019)
Due to their strong antimicrobial activity, silver nanoparticles (AgNPs) are massively produced, applied, consumed and, as a negative consequence, released into wastewater treatment plants. Most AgNPs are assumed to be bound by sludge, and thus bear potential risk for microbial performance and stability. In this lab-scale study, flow cytometry as a high-throughput method and 16S rRNA gene amplicon Illumina MiSeq sequencing were used to track microbial community structure changes when being exposed to AgNPs. Both methods allowed deeper investigation of the toxic impact of chemicals on microbial communities than classical EC50 determination. In addition, ecological metrics were used to quantify microbial community variations depending on AgNP types (10 and 30 nm) and concentrations. Only low changes in α- and intra-community ß-diversity values were found both in successive negative and positive control batches and batches that were run with AgNPs below the EC50 value. Instead, AgNPs at EC50 concentrations caused upcoming of certain and disappearance of formerly dominant subcommunities. Flavobacteriia were among those that almost disappeared, while phylotypes affiliated with Gammaproteobacteria (3.6 fold) and Bacilli (8.4 fold) increased in cell abundance in comparison to the negative control. Thus, silver amounts at the EC50 value affected community structure suggesting a potential negative impact on functions in wastewater treatment systems.